Burden of venous leg ulcers in the United States. (May 2014) - Rice, J. Bradford; Desai, Urvi; Cummings, Alice Kate G.; Birnbaum, Howard G.; Skornicki, Michelle; Parsons, Nathan
Abstract Objective: To estimate the annual incremental per-patient and overall payer burden (2012USD) of venous leg ulcers (VLU) in the US. Methods: Beneficiaries with and without VLU were identified using two de-identified insurance claims databases: aged 65+ from a 5% random sample of Medicare beneficiaries (2007–2010: n ∼ 2.3 million); and aged 18–64 from a privately-insured population (2007–2011: n ∼ 8.4 million). The index date was selected as the date of a VLU claim with no other VLU diagnoses in the preceding 12 months for the VLU cohort and as the date of a random medical claim for the non-VLU patients. These groups were matched using propensity scores to account for differences in demographics, comorbidities, resource utilization, and costs in the 12 month pre-index period. Medical resource use and costs incurred during the 12 month follow-up period were calculated for both payers. Drug costs and indirect work-loss due to disability and medically-related absenteeism were estimated for the privately-insured sample only. Annual VLU incidence rates were also estimated for both payers. Results: Data for 58, 672 matched VLU/non-VLU pairs of Medicare and 22, 476 matched pairs of privately-insured patients were analyzed. Relative to matched non-VLU patients, VLU patients used more medical resources and incurred annual incremental medical costs of 6391 in Medicare (18, 986 vs 12, 595), and 7030 (13, 653 vs 6623) in private insurance (7086 including drug costs). Compared with non-VLU patients, privately-insured VLU patients had more days missed from work (14.0 vs 10.0), resulting in 29% higher work-loss costs (comparisons significant at p < 0.0001). The average annual incidence rate of VLU was 2.2% in Medicare and 0.5% in private insurance. Limitations: Findings did not account for out-of-pocket payments or other indirect costs (e.g., lost productivity), and relied on accuracy of diagnosis and procedure codes contained in claims data. Conclusion: These findings suggest an annual US payer burden of 14.9 billion.